Is there a place for dexmedetomidine in equine anaesthesia and analgesia? A systematic review (2005–2017) - Gozalo-Marcilla, M. [UNESP]; Gasthuys, F.; Luna, S. P.L. [UNESP]; Schauvliege, S. (Wiley, 2018)
The objective of this review was to perform a literature compilation of all the equine publications that used dexmedetomidine as the first article on this topic was published, in 2005. We also aimed to answer the question whether the use of dexmedetomidine can currently be justified. For that, we compiled information from databases, such as PubMed, Google Scholar and Web of Science and the proceedings of the last veterinary anaesthesiology meetings. Dexmedetomidine is an attractive drug to be used in horses, mainly due to its pharmacokinetic profile and pharmacodynamics that favour its use as intravenous constant rate infusion (CRI). Nowadays, its clinical use is popular for sedation in prolonged standing procedures and during partial intravenous anaesthesia (PIVA) and total intravenous anaesthesia (TIVA). However, legal requirements for its use should be taken into account.